Multiplex MPN-PCR for the enumeration of three major Vibrios in raw fishes in Malaysia - Bonny, Sharmin Quazi; Hossain, M.A. Motalib; Thong, Kwai Lin; Ali, Md. Eaqub (Elsevier, 2018)
Vibrio parahaemolyticus, Vibrio cholerae and Vibrio vulnificus are the most notorious fish borne-pathogens responsible for several deadly diseases in human. However, the prevalence of these three pathogenic vibrios in Malaysian fishes has not been thoroughly investigated, leaving a study gap for the tracing of possible Vibrio outbreak through carrier fish consumption. The most-probable-number-PCR (MPN-PCR) assays are highly sensitive for the identification of a single bacterial pathogen but they have not been applied for the discrimination of major vibrios in a multiplex platform. This study coupled MPN method with Multiplex PCR to differentiate three major vibrios in a one test platform. A total of 120 fish samples were analyzed and the prevalence of V. parahaemolyticus, V. cholerae, and V. vulnificus was 48.33%, 27%, and 32.50%, respectively. When simplex MPN-PCR was applied similar results were obtained at P < 0.05, validating the accuracy of multiplex MPN-PCR. The microbial loads of V. parahaemolyticus, V. cholerae, and V. vulnificus in the tested samples were 0–2.43 × 106, 0–2.16 × 106, and 0–4.93 × 105 MPN g−1, respectively. Primers based on housekeeping pntA gene amplified V. parahaemolyticus (409 bp) and V. cholerae (338 bp) but virulent vvhA gene detected V. vulnificus (205 bp). Thus the 27–48% prevalence of targeted vibrios in consumable fishes indicated there is considerable risk of Vibrio onset in Malaysia due to the consumption of undercooked or raw fish products.